The impact of TED Talk videos on students’ presentation performance - Kaҫauni, Dorela; Robo, Lorena (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study investigated the impact of Technology, Entertainment, and Design (TED) Talk videos on students’ presentation performance within the higher education context. Employing a quantitative approach, the study involved 14 first-year students enrolled in a “bachelor in English language” program at “Fan S. Noli” University, Korça, Albania. The research, conducted during the academic year 2022-2023 in “text analysis 1 and 2” modules, explores how the sequential exposure to TED Talk videos influences students’ presentation skills. After watching the initial TED Talk video, students prepared and delivered one presentation, assessed using a rubric. Subsequently, students viewed 10 more TED Talk videos, with two presentations following these viewings. The study’s analysis was facilitated using the statistical package for the social sciences (SPSS) version 20 software program. The Friedman and the Wilcoxon signed-rank tests were used to determine whether there are statistically significant differences among the groups in the repeated-measure design. The findings demonstrate that TED Talk videos play a significant role in enhancing students’ presentation skills. This research contributes to the ongoing discourse on multimedia-enhanced pedagogy and the efficacy of integrating TED Talk as an educational resource, with SPSS version 20 aiding in the quantitative analysis of the obtained data.